Relações diferenciais entre tensões e correntes de circuitos π com resistência de amortecimento - Jús, Luis Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This paper describes the mathematical modeling of a single phase transmission line based on electrical circuits described by concentrated and frequency independent parameters. This single-phase representation of a transmission line is approximated by means of a π circuit cascade with damping resistors in all circuit units in order to smooth the numerical oscillations present in the simulation results when energizing this model. Along, it is discussed the use of an alternative method to construct the modeling matrices, also with the intention of smoothing Gibbs oscillations and increase the range of results that are numerically stable. During the paper, the mathematical representation of this cascade is discussed through state equations. The development of the state equations is the main objective in this paper and will result in differential relations between the currents and voltages for each π circuit of the cascade. During this development, differences will be observed between specific circuits, which will result in three different equations depending on the position of these circuits in the cascade. Finally, there are some final considerations and it is suggested the stages for future works, which involve the development of the numerical method and the numerical routine, which aims to improve the results of simulations using this type of structure, reducing the influence of undesirable numerical oscillations that are generated by the numerical solution method of the mathematical model

Neste trabalho é estudada a modelagem matemática monofásica de uma linha de transmissão baseada em circuitos elétricos descritos por parâmetros concentrados e independentes da frequência. Essa representação monofásica de linhas de transmissão é aproximada por meio de uma cascata de circuitos π com resistências de amortecimento em todas as unidades de circuitos, a fim de suavizar as oscilações numéricas presentes nos resultados das simulações de energização desse modelo. É discutida a utilização em conjunto de um método alternativo para construção das matrizes de modelagem, também com a intenção de suavizar as oscilações de Gibbs e ainda aumentar o alcance de resultados numericamente estáveis. Durante o trabalho, é desenvolvida a representação matemática dessa cascata por meio de equações de estado. O desenvolvimento das equações de estado é o principal objetivo neste trabalho e resultará em relações diferenciais entre as correntes e tensões para cada circuito π dessa cascata. Durante esse desenvolvimento, serão observadas diferenças entre circuitos específicos, o que resultará em três diferentes equacionamentos, que dependem da posição desses circuitos na cascata. Por fim, são feitas algumas considerações e são sugeridas as etapas para trabalhos futuros, que envolvem o desenvolvimento do método numérico eda rotina numérica, tendo o objetivo de melhorar os resultados das simulações que utilizam esse tipo de estrutura, diminuindo a influência de oscilações numéricas que são geradas pelo método numérico de solução do modelo matemático
Differential relationships between voltages and currents of π circuits with damping resistance
Keywords: Circuitos eletricos; Equações de estado; Linhas de telecomunicação; Oscilações; Telecomunicações; Electric circuits; Equations of state; Oscillations; Telecommunication; Telecommunication lines